Design, Development and Evaluation of Aceclofenac Matrix Tablet Using Eudragit and Carbopol as Matrix Forming Agents - Chatterjee, Arindam; Patel, Alok M; Gupta, Rakesh Kumar; Mishra, Anuj (Journal of Biomedical and Pharmaceutical Research, 2022)
Aceclofenac is a non-steroidal anti-inflammatory, analgesic and antipyretic agent. It has short biological half-life (4 hours). The present study aims to formulate sustained release Matrix tablet of Aceclofenac for improved patient compliance, better therapeutic efficacy, less side effects and reduced dosage regimen with less toxicity. Total six formulations (F1-F6) were prepared with varying ratios of Eudragit RS100 and Carbopol 934P as matrix forming agents and evaluated for various pre-compression and post compression parameters. Formulation (F3) containing 1:1 ratio of Eudragit RS100 and Carbopol 934P showed promising results in dissolution studies when compared to the rest of the formulations.Keywords: Aceclofenac, Matrix Tablets, Eudragit, Carbopol, Sustained Release.